Analisis Penanganan Kerusakan Jalan Menggunakan Metode Pavement Conditional Index (PCI) dan Bina Marga Pada Ruas Jalan Kabuh - Muhammad Dimas Widyanto (Asosiasi Riset Ilmu Teknik Indonesia, 2023)
In human life, roads have an important role as a means of land transportation (Kristina et al., 2021), especially to support national development in the economic and socio-cultural fields. Apart from that, highways also act as community mobility, requiring good service in line with capacity requirements (Rahmanto, 2016). If there is damage to the road it can cause an accident. So it is necessary to improve the quality of roads and road infrastructure to increase the safety and comfort of road users.